DERMATOLOGICAL ZOONOSES IN PET HEDGEHOGS: A ONE HEALTH-BASED SYSTEMATIC REVIEW - Parahita, Astrid Laboure; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2026)
The African pygmy hedgehog (Atelerix albiventris) is an exotic animal that has become increasingly popular as a pet in Indonesia. Despite its unusual appearance and being rarely handled directly, this animal poses a risk of transmitting zoonotic dermal diseases to humans. Transmission often occurs unnoticed and is frequently overlooked by both pet owners and the general public. This study aims to examine the risk of zoonotic skin diseases transmitted by mini hedgehogs and emphasize the importance of a One Health approach in their control. This review was conducted using a systematic literature review method on scientific articles obtained through Google Scholar, PubMed, ScienceDirect, and ResearchGate. A total of 25 relevant literatures were selected based on topic relevance, scientific quality, and accessibility. The review findings indicate that several pathogens such as Trichophyton erinacei, Sarcoptes scabiei, Cryptosporidium spp., and Enterocytozoon bieneusi have been found in mini hedgehogs and can potentially cause diseases in humans. Transmission may occur through direct contact, contaminated cage equipment, or the environment. The public’s limited understanding of exotic animals increases the risk of zoonotic transmission. In conclusion, mini hedgehogs are a potential source of zoonotic diseases that is often underestimated. A One Health approach is crucial to prevent and control the spread. Continuous public education and active involvement of veterinarians are necessary to detect and prevent zoonotic diseases originating from exotic pets.